A Critical Study of Islamic Philosophy: An Attempt to Reconstruct The Dogma of Absolutism of Truth (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
All forms of knowledge and truth in essence are not really the complete truth, there are always aspects of weakness and shortcomings, even in the field of science that is considered the mother of all knowledge or what is called philosophy itself. If there are no shortcomings from the ontological side (the essence of science), there must be shortcomings from the epistemological side or both completely, for example, then there will definitely be a weak side in the axiological field. Thus, it is necessary to continuously conduct studies or deepening of all existing fields of knowledge without exception to maintain the preservation of knowledge in the life of the human race. Truth is a reference for all forms and models of science to bridge the neutrality of science as an object of analysis that will remain open to all forms of criticism and change in order to continuously give birth to truths. There is no final word in a truth and no field of science has the right to claim truth as the single truth to the reality that is widespread in the life of mankind. Truth is the truth itself. This, not only for one particular scientific field, such as the field of philosophy, for example, is also not a reflection of some other sciences. Philosophy as the parent of science is not automatically a certain field that can claim a single truth, in fact there are many gaps to position philosophy as a field of ancient science that leaves many problems related to the validity of truth that has many faces or many variants in it. We will find the completeness of the truth in the owner of the truth himself. As for the others, it is an overflowing shadow of the owner of the truth himself. The approach in this critical study of philosophy, the author focuses more on religious criticism of some logical deviations or philosophical perspectives from the perspective of sharia, where it has tarnished the truth of religion through the postulates of truth that have been informed by religion through revelation texts. Exposing the falsehood of the burhani postulates possessed by philosophy by presenting argumentative evidence of religion on several existing philosophical problems, especially the logical rebuttal data put forward by Al-Gazali on several issues that are considered deviant from the philosophical way of thinking by several Greek philosophers represented by Ibn Sina and al-Farabi in the Islamic world.
Keywords: Studies; Critical; deconstruction; dogmatic and philosophical